Minicomputers in Homœopathy - De Ruyter, E.A.A.A.D. (British Homeopathic Journal, 1976)
Repertory analysis of homœopathic cases has always been very time-consuming. For this reason homœopathic doctors have often had to restrict themselves to searching for the most likely remedies from a total of frequently as few as 50 most common remedies. The use of a relatively inexpensive minicomputer for repertory selection from a total of 352 homœopathic remedies based on the 501 most common symptoms from Boericke's Repertory is described. This procedure greatly reduces the time needed for and improves the accuracy of repertory analysis.